Assessment of the "Second Day" Exercise Effect on Glycemic Control, Insulin Requirements, and CHO Intake in Type 1 Diabetes Adults. (January 2021) - Müller-Korbsch, Michael; Frühwald, Lisa; Heer, Michael; Fangmeyer-Binder, Maria; Reinhart-Mikocki, David; Fasching, Peter
Background: Glucose control during consecutive days of aerobic exercise has not been well studied. We assessed glycemia, insulin requirements, and carbohydrate (CHO) needs during two consecutive days of prolonged cycling in type 1 diabetes (T1D) adults using sensor-augmented insulin pump therapy. Methods: Twenty adults with well-controlled T1D and six healthy adults (for comparison) were enrolled. Assessments were made during two consecutive days of cycling activities (30 miles per day). On day 1 (D1), basal rates were reduced 50% and CHO intake was guided by real-time continuous glucose monitoring (rtCGM) data to maintain a target range (70-180 mg/dL). On day 2 (D2), basal insulin infusion was stopped for the first hour of biking and resumed at a minimal rate during biking. Carbohydrate intake one hour before, during, and ten minutes after biking was recorded. Times within/below target range, glycemic variability, and mean glucose were calculated from rtCGM data. Results: Among 17 T1D participants who completed the study, mean glucose levels at the start of cycling were slightly lower on D2 vs D1: 138 ± 16 mg/dL and 122 ± 16, respectively, P = NS. Type 1 diabetes participants achieved near-normal glucose levels at the end of both cycling events; however, the reduction in glucose was most notable at one hour into the event on D2 vs D1. Carbohydrate intake was notably lower during D2 vs D1 with no difference in time <54 mg/dL (both P = NS). Conclusions: Type 1 diabetes individuals using rtCGM-augmented insulin pump therapy can safely engage in consecutive days of prolonged aerobic exercise by significantly reducing insulin dosages with no increase in CHO intake.